New perspectives on the roles of Abl tyrosine kinase in axon patterning - Ramakrishnan Kannan; Edward Giniger (Fly, 2017)
The Abelson tyrosine kinase (Abl) lies at the heart of one of the small set of ubiquitous, conserved signal transduction pathways that do much of the work of development and physiology. Abl signaling is essential to epithelial integrity, motility of autonomous cells such as blood cells, and axon growth and guidance in the nervous system. However, though Abl was one of the first of these conserved signaling machines to be identified, it has been among the last to have its essential architecture elucidated. Here we will first discuss some of the challenges that long delayed the dissection of this pathway, and what they tell us about the special problems of investigating dynamic processes like motility. We will then describe our recent experiments that revealed the functional organization of the Abl pathway in Drosophila neurons. Finally, in the second part of the review we will introduce a different kind of complexity in the role of Abl in motility: the discovery of a previously unappreciated function in protein secretion and trafficking. We will provide evidence that the secretory function of Abl also contributes to its role in axon growth and guidance, and finally end with a discussion of the challenges that Abl pleiotropy provide for the investigator, but the opportunities that it provides for coordinating biological regulation.